Propionimicrobium lymphophilum in urine of children with monosymptomatic nocturnal enuresis - Naoto Nishizaki; Satoshi Oshiro; Mari Tohya; Shin Watanabe; Tadaharu Okazaki; Ken Takahashi; Teruo Kirikae; Teruo Kirikae; Toshiaki Shimizu (Frontiers in Cellular and Infection Microbiology)
BackgroundDespite a unique microbiome in urine, the relationship between nocturnal enuresis and the urobiome remains unclear. This study aimed to compare the presence of specific bacterial species in the urine of children with and without nocturnal enuresis.MethodsWe used 16S ribosomal RNA gene sequencing to analyze the urobiome in urine samples obtained from the two groups of children. The presence of Propionimicrobium lymphophilum was examined using real-time PCR in the urine of 25 children diagnosed with monosymptomatic nocturnal enuresis (MNE), and 17 children without this condition.ResultsChildren with MNE exhibited a significantly higher prevalence of P. lymphophilum: 16 out of 25 (64.0%) compared to 4 out of 17 (23.5%) in the control group. Among children with frequent bedwetting, there was a significantly higher prevalence of P. lymphophilum;15 out of 16 (93.8%) compared to 2 out of 9 (22.2%) in those with infrequent bedwetting. Bacterial culture tests confirmed the anaerobic growth of P. lymphophilum isolates from urine samples of two PCR-positive patients with MNE. These isolates were found to be susceptible to ampicillin.ConclusionThese findings suggest that P. lymphophilum may be associated with chronic urinary tract infections and potentially contribute to the development of MNE in children.